THE PERSONALITY STRUCTURE OF CHARACTERS IN THE ROMAN THÉRÈSE RAQUIN BY ÉMILE ZOLA (A PSYCOANALYSIS STUDY) - Grace Shirley Luntungan; Helena Mirthe; Conny Renny Lasut (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
The subject of this research is the novel Thérèse Raquin by Émile Zola published by Librairie Generale Francaise – Les Classiques D'aujourd'hui N° 34, November 3, 1971. The main object of this research is (1) the personality structure in the main character and auxiliary characters. Additional research objects are (2) related intrinsic elements (such as characters, characterizations and themes) to affirm research results. The approach used in this research is a psychological approach with Sigmund Freud's psychoanalytic theory, and the research method used is descriptive-qualitative research method. This study aims to describe the personality structure of the main and auxiliary characters in the novel Thérèse Raquin by Émile Zola by using psychoanalytic theory in Sigmund Freud's literary work. The results of this research from the psychological analysis of the main character and auxiliary characters, it was found that (1) the personality of the superego in Thérèse as the main character is more dominant than the ego and id. While the overall personality of id in Laurent's as auxiliary character is more dominant than his ego and superego. Thérèse's character is depicted as a submissive and passive woman, while Laurent's character is portrayed as the opposite. (2) The major theme in this novel is infidelity, and the minor theme is murder.